Shadow kiss - Mead, Richelle (Vampire Academy, 2008)
While Rose is coping with the darker effects of being shadow-kissed, her relationship with Dimitri is finally taking off, and when he disappears during a Strigoi attack on St. Vladimir's Academy, she must make a terrible choice.
Keywords: nuortenkirjallisuus; nuorten aikuisten kirjat; vampyyrit